Effects of brief intervention on the alcohol consumption pattern of Primary Health Care users (Research, Society and Development, 2022)
This work aims to analyze the effects of brief intervention on alcohol consumption in the context of APS. Alcoholism and problems related to its abusive use are configured as one of the main public health problems. This is a randomized-controlled, parallel, open, unblinded Clinical Trial conducted in the community with the objective of meeting the needs of the population assigned to a specific space. The study evaluated the outcome of interventions in alcohol users who received BI and in the control group, composed of alcohol users who received only screening with application of the AUDIT instrument. The study had three phases: screening phase, intervention/control phase and post-intervention phase for evaluation with a follow-up of six months, carried out in two moments: one month and six months after the first intervention. The study allowed to identify a change in the pattern of alcohol consumption by users who participated in the intervention, but not substantially in relation to the pattern of the AUDIT, which shows a change in the number of doses consumed, facilitating the interpersonal relationship between patients because it increases the affective bond between the user and the health team, it is essential that health professionals are increasingly focused and inserted in the spaces where they work so that they exercise, with quality, their functions of preventing, treating, rehabilitating and educating their users.